PRINCIPLES OF LEASE RELATIONS OF UNIVERSITIES - Tamara N. Konchenkova (Вестник Российского экономического университета имени Г. В. Плеханова)
Handing-over the property of annexed universities is a serious problem for education institutions. The article discusses issues connected with lease relations in today’s conditions. Special attention is paid to the process of handing-over the property through auction and without it. Apart from that the author describes procedures of concluding a lease on preferential terms in order to systematize lease relations for effective use of education institution infrastructure and raising the university image. The author proposes a scheme showing stages of handing-over property on preferential terms and identifies all steps of interaction between leaser and founder of the education institution.